Modern Inorganic Chemistry / Fourth Edition - Liptrop G. F. (Bell and Hyman, 1985)
Preface, Bibliography, Acknowledgements, Early Theoretical Background of Chemistry and the Determination of Atomic Weights, The Periodic Classification of Elements, The Structure of the Atom, The Arrangement of Electrons in Atoms, Chemical Bonds, Chemical Geometry, Modern Valency Theory, Oxidation and Reduction, Acids and Bases, Occurence and Extraction of Metals, The First Transition Series (Scandium - Titanium - Vanadium - Chromium - Manganese - Iron - Cobalt - Nicket), Some More Features of the First Transition Series, The First Inner Transition Series (The Lantanides), Nuclear Chemistry, Answers to Questions, Index, Table of Atomic Weights, Logarithm and Antilogarithm Tables.